Synthesis of Diazo Quinolinone - Stefan Marco Rumengan; Khoirotul Ummah; Robby Gus Mahardika; Ana Mardliyah; Mariam Ulfah; Ajeng Triane Syawila (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
Quinolones are important heterocyclic compounds in medicine and materials for DSSC or OLED. This study aims to make a quinolinone framework that has several functional groups. These functional groups can be coupled with various other heterocyclic compounds. The synthesis of the target compound consists of forming a quinolinone framework using phenyldiamine and ethyl aceto acetate via the Penchmann reaction then iodination using ICl. The Penchmann reaction succeeded in forming a quinolinone framework as indicated by shown a proton signal at 11.22 ppm. The iodination reaction was successfully carried out by adding iodo to the benzene ring and the appearance peak of (M+H) m/z was 300.9839 on mass spectroscopy. The compound 7-amino-8-iodo-4-methyl-2-quinolinone (compound 2) has been successfully synthesized. Compound 2 has 3 functional groups (amine, iodo and alkene) that can be used for coupling with the other heterocycles.